PENGARUH PEMBELAJARAN AQIDAH AKHLAK TERHADAP PERILAKU SISWA KELAS VIII3DI MADRASAH TSANAWIYAH PONDOK PESANTREN NURUL ISLAM KAMPUNG BARU KECAMATAN GUNUNG TOAR - Rabuanim Rabuanim; Andrizal Andrizal; Helbi Akbar (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
This study aims to determine the effect of Aqeedah Moral Learning Against Behavior of Class VIII3 Students in MTs. PP Nurul Islam Kampung Baru, Gunung Toar District. This research is a qualitative study using quantitative data that is quantitative then using a Likert scale with a scale of 1-5. Based on the results of the study it can be concluded that the learning of moral aqidah has a significant effect on the behavior of students of class VIII3 in MTs. PP Nurul Islam Kampung Baru, Gunung Toar District and the indicators in this study are valid. Aqidah ahklak learning variable has a very strong and positive relationship with the behavior of grade VIII3 students in MTs. PP Nurul Islam Kampung Baru, Gunung Toar District.